The Effectiveness of a Health Promoting Behavior Program for Elderly with High Blood Pressure at Banklong Sub District Health Promoting Hospital, Phitsanulok - สิทธิสาตร์, วิภาพร; มีทิพย์, นิดา; อินจีน, จันทร์จิรา (Nursing Journal of The Ministry of Public Health, 2019)
Hypertension is a common non-communicable disease and a leading cause of death among Thai elder people. The purposes of this quasi-experiment research were to compare health promoting behaviors and blood pressure scores among elder people before and after participating in a health promoting behavior program. The sample consisted of 45 older persons with hypertension who had blood pressure not more than 160/100 mmHg and treated at Banklong Sub District Health Promoting Hospital. The systematic random sampling method was used to select sample. The health promoting program was performed 4 times for 4 months. Data were collected by using the health behavior interview. Demographic data were analyzed by using frequency, percentage, mean, and standard deviation. Health behaviors and blood pressure levels were compared before and after the program by using t-test. The results of the study showed that elderly had significantly higher average posttest scores of health promotion behaviors than pretest and had significantly lower systolic and diastolic blood pressure scores at end of the program than before starting the program at p<.05.